Uruguay adoptó norma europea. (Chasqui (13901079))
The article discusses Uruguay's decision to adopt the European DVB-T standard for television service. The country decided upon using the standard after consulting with various social and business sectors that formed a National Commission for Digital Television which monitored the digitalization process. According the the Uruguayan sub-secretary for industry, the move will allow the country to proceed with other opportunities for technological advancement, including the production of software and other applications.